Penguatan Literasi Etika Artificial Intelligence bagi Anak dan Pendidik dalam Mewujudkan Pendidikan Digital yang Bertanggung Jawab - Imelda Martinelli; Rezita Rahmatia Antu; Cecilia Elizabeth Longdong; Tesalonika Valerie Limmartin (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
This Community Service Program (PKM) aims to enhance ethical AI literacy among students and educators to support responsible digital education. The activity employs an educative-participatory approach through four stages: preparation, implementation, evaluation, and reporting. The content covers basic AI concepts, benefits, risks, ethical use, data privacy, and legal aspects. Participants engage in interactive discussions, case studies, responsible AI simulations, and Q&A sessions. The results show improved understanding of ethical AI use, the importance of information verification, maintaining academic integrity, and protecting personal data. Participants can distinguish permissible AI applications from those that may violate ethical standards and recognize AI as a learning aid rather than a substitute for critical thinking. This activity strengthens AI ethical literacy and contributes to creating a safe, responsible, and ethical digital learning ecosystem.